Analysis of the Implementation of the Combination of the Talaqqi Method and the Ummi Method in Improving Al-Qur'an Reading Skills in Elementary Schools - Arifah Nurbaiti Diyah Ayu Ariningrum; Ratnasari Diah Utami (Universitas Ahmad Dahlan, 2026)
Efforts to improve Al-Qur’an reading skills through implementing a combination of talaqqi and ummi methods. The aim of the research is to determine the process of implementing Al-Qur'an learning and improving Al-Qur’an reading skills using a combination of talaqqi and ummi methods for students. The research was conducted by applying a descriptive qualitative method and subjects were taken using a purposive sampling technique. Data was taken using observation, interview and documentation techniques and then tested for validity using data triangulation. Next, data analysis techniques is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results are 1) The implementation of a combination of talaqqi and ummi methods in improving Al-Qur’an reading skills has succeeded in creating students who meet the indicators to be said to be capable of reading the Al-Qur'an; 2) Its effectiveness can be seen from increasing skills in reading the Al-Qur'an, such as fluency, accuracy of recitation, and makhorijul letters. Challenges arise such as teacher limitations and differences in students' ability to remember letter shapes so that they do not meet the indicators. Training for tutors and assistance from parents when studying at home will maximize students’ skills in reading the Al-Qur’an.